A prelimary assesment of the colonization of benthic communities - عربية, عزت; ازدهار عمار; عبد اللطيف علي (Latakia University Journal -Biological Sciences Series, 2024)
This study provided quantitative data on the early succession of macrobenthose on artificial reefs (ARs) placed in the infralittoral zone at a depth of 10 to 15 m at the Ibn Hani site north of Latakia on the Syrian coast during the period 2021-2023. 30 species have been recorded on the artificial reefs, and 22 alien species. Bugula neritina (Linnaeus, 1758) of Bryozoa and Telmatactis panamensis (Verrill, 1869) of Cnidarians are recorded for the first time in the eastern Mediterranean basin. Visual quadrats were used to describe the establishment and development of communities. The study extended over a three years after the immersion of the (ARs), and included 9 field trips, in which some species of Macroalgae and some species of sessile invertebrates appeared, which showed different patterns of abundance during the study period. The results of this study indicate that ecological succession is still ongoing, and further improvement in monitoring methodology could help to more accurately assess the composition of artificial reef communities